Transformasi Pembelajaran Multibahasa di Era Society 5.0 : Bentuk Sistem Pembelajaran One Teacher One Language pada Pendidikan Anak Usia Dini - Andari, Ida Ayu Made Yuni; Antara, Putu Aditya; Asril, Nice Maylani; Dwipadmini, Ade Lestari (Institut Agama Hindu Negeri Gde Pudja Mataram, 2025)
The transformation of language learning in early childhood education has become an important issue in the discourse of education in the Society 5.0 era, which emphasizes the integration of technology and human values. This article discusses the implementation of the One Teacher One Language (OTOL) system as a strategic approach in creating a multilingual learning environment at TK Nasional 3 Bahasa Budi Luhur. The purpose of this research is to analyze the implementation of the One Teacher One Language (OTOL) system, its supporting systems, and the role of facilities in creating a consistent learning ecosystem for three languages: Indonesian, English, and Mandarin. This research uses a qualitative approach with a case study design, involving observation, in-depth interviews, and documentation analyzed using NVivo 14 software through the stages of open coding, axial coding, and selective coding. The findings show that OTOL is implemented systematically through the division of teacher roles, cultural integration, facility enhancement, and parental involvement, despite facing challenges in coordination and continuity between sessions. The main contribution of this article lies in the empirical mapping of how OTOL can become a transformative learning model in multilingual education based on the values of Society 5.0. These results are important for strengthening early childhood education practices amid the demands of globalization, as well as serving as a strategic reference for the development of contextual and sustainable multilingual education curricula and policies.